Reformulation of the Approval of the Honorary Council of Notaries in Providing Recommendations for the Interests of the Court - Tri Wahyudiono; Ermanto Fahamsyah; Bhim Prakoso; Gatot Eddy Pramono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Notary Honorary Council as a new organ that emerged in the Amendment to the UUJN has become a crucial organ in the law enforcement process for the benefit of the judiciary and its efforts to maintain the nobility and dignity of the Notary Office, this is because of the approval or rejection issued by the MKN at the request of investigators, public prosecutors or judges when they want to take a photocopy of the Minutes of the Deed and/or summon a Notary related to the Deed or Notary Protocol that is in the Notary's storage. This article provides an understanding of the actual characteristics of the MKN's authority and what the MKN's recommendation formulation is in order to maintain the honor of the Notary Office and uphold the judicial process. The results of the analysis found that the MKN's authority to provide approval or rejection of requests from investigators, public prosecutors, or judges for the benefit of the judiciary and the authority in terms of guiding as referred to in Article 66 and Article 66A of the Amendment to the UUJN is categorized as attributive authority based on several reasons: Authority granted by law; Authority that cannot be transferred; and Special purpose of authority. Meanwhile, the MKNW recommendation formulation for approval or rejection is in the form of a final and binding state administrative decision, and there are no Administrative Efforts. Clear procedures serve to realize legitimacy, transparency, and responsibility as well as the protection of the rights and interests of Notaries. The structure of the recommendation for approval or rejection made by the MKNW can at least include: the identity of the parties involved, the legal basis for the application, a description of the request, considerations and reasons for approval, limitations and provisions, the validity period of the approval, signatures, and official stamps.